1999
DOI: 10.1063/1.479521
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy of methanol and acetonitrile clusters in cold helium droplets

Abstract: Structure and hydration of the C4H4 •+ ion formed by electron impact ionization of acetylene clustersInfrared molecular beam depletion spectroscopy of small methanol and acetonitrile clusters embedded in large helium clusters has been studied in the spectral region of the CO stretch and the CH 3 rock mode from 1023 to 1059 cm Ϫ1 . The results are compared with the experimental spectra of the corresponding free clusters generated in adiabatic expansions and calculations based on density functional theory or emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
2
7

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 44 publications
(46 reference statements)
4
62
2
7
Order By: Relevance
“…On the other hand, the average slope of about 0.4 found for the heavy systems, indicates an average factor of 2.5 increase in the moments of inertia, which is attributed to a stronger coupling of the molecular rotation to the helium bath. Homogeneous clusters which have been studied in the IR region include (SF 6 ) n [130,144] (n = 2-4), (HCCCN) 2 , [136] (CH 3 OH) n n = 2-5, [176] (CH 3 CN) n n = 2-6, [176] (HCN) n n = 2-7, [145,146] (HF) n n = 2-8, [177][178][179] and (H 2 O) n n = 2-6. [180][181][182] The number of heterogeneous van der Waals complexes studied is even larger and includes such systems as HCN-H 2 (parahydrogen (pH 2 ), ortho-hydrogen (oH 2 ), para-deuterium (pD 2 ), ortho-deuterium (oD 2 ), HD), [183,184] HCN-C 2 H 2 , [185] HCN-Mg n (n = 1-3), [152,186] HF-H 2 (pH 2 , oH 2 , pD 2 , oD 2 , HD), [187,188] and HF-Ar n (n = 1-6) (Ne,Kr), [189] and OCS-(H 2 ) n (n = 1-17).…”
Section: Free Rotations Of Molecules and Clusters In Heliummentioning
confidence: 99%
“…On the other hand, the average slope of about 0.4 found for the heavy systems, indicates an average factor of 2.5 increase in the moments of inertia, which is attributed to a stronger coupling of the molecular rotation to the helium bath. Homogeneous clusters which have been studied in the IR region include (SF 6 ) n [130,144] (n = 2-4), (HCCCN) 2 , [136] (CH 3 OH) n n = 2-5, [176] (CH 3 CN) n n = 2-6, [176] (HCN) n n = 2-7, [145,146] (HF) n n = 2-8, [177][178][179] and (H 2 O) n n = 2-6. [180][181][182] The number of heterogeneous van der Waals complexes studied is even larger and includes such systems as HCN-H 2 (parahydrogen (pH 2 ), ortho-hydrogen (oH 2 ), para-deuterium (pD 2 ), ortho-deuterium (oD 2 ), HD), [183,184] HCN-C 2 H 2 , [185] HCN-Mg n (n = 1-3), [152,186] HF-H 2 (pH 2 , oH 2 , pD 2 , oD 2 , HD), [187,188] and HF-Ar n (n = 1-6) (Ne,Kr), [189] and OCS-(H 2 ) n (n = 1-17).…”
Section: Free Rotations Of Molecules and Clusters In Heliummentioning
confidence: 99%
“…High power line-tunable gas lasers, cw or pulsed, are still being used up to the present time [59,60,61,62]. Because of the sparse set of available lasing frequencies, they are most suited to the investigation of small molecules, with small moments of inertia and therefore well spaced lines.…”
Section: Radiation Sourcesmentioning
confidence: 99%
“…In liquid helium there is a low-barrier pathway, which allows the insertion of a water molecule into a trimer ring. For methanol clusters in liquid helium Buck and co-workers [29] showed that once the cyclic trimer is formed and cooled, insertion of the fourth molecule into the ring is inhibited by the lack of energy available to open the ring. In our study cyclic trimers and tetramers are formed, but the formation of larger cyclic structures is not seen.…”
mentioning
confidence: 99%